2011
DOI: 10.1021/ic2011315
|View full text |Cite
|
Sign up to set email alerts
|

Group 6 Complexes with Iron and Zinc Heterometals: Understanding the Structural, Spectroscopic, and Electrochemical Properties of a Complete Series of MM···M′ Compounds

Abstract: Binuclear quadruply bonded complexes Cr(2)(dpa)(4) (1, dpa = 2,2'-dipyridylamide), Mo(2)(dpa)(4) (2), and W(2)(dpa)(4) (3) react with anhydrous FeCl(2), yielding heterometallic compounds CrCrFe(dpa)(4)Cl(2) (4), MoMoFe(dpa)(4)Cl(2) (5), and WWFe(dpa)(4)Cl(2) (6). These molecules are structurally similar, having a linear M≡M···Fe chain that is axially capped by chloride ions and is equatorially supported by the helically twisted dpa ligands. A structurally related zinc analog, CrCrZn(dpa)(4)Cl(2) (7), can be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 81 publications
1
67
0
Order By: Relevance
“…[38][39][40][41] Their work has provided a great insight into HMSCs that may have potential in many important catalytic applications, from heterometallic enzyme active sites to alloys or mixed metal oxides in heterogeneous catalysis.…”
Section: A -M a -M B Hmscsmentioning
confidence: 99%
See 2 more Smart Citations
“…[38][39][40][41] Their work has provided a great insight into HMSCs that may have potential in many important catalytic applications, from heterometallic enzyme active sites to alloys or mixed metal oxides in heterogeneous catalysis.…”
Section: A -M a -M B Hmscsmentioning
confidence: 99%
“…The synthetic strategies for the preparation of M A -M A -M B HMSCs reported by Berry. [38][39][40][41]43] . Adapted with permission from ref.…”
Section: A -M a -M B Hmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterometallic compounds synthesized to date fall into three classes as has been previously suggested: [40] 1) symmetric M (22), [76] was prepared from the reaction of quadruply bonded Cr 2 (dpa) 4 and divalent FeCl 2 in refluxing THF. [40,77] Mn II , [78] Fe II , [78,79] Co II , [80] Ni II , [81] and Zn II , [79] ions have been made. In most cases, partial σ bonding delocalization throughout the chain is achieved.…”
Section: Monometallicmentioning
confidence: 99%
“…A variable temperature 1 H NMR study on the Cr 2 Zn(dpa)4 Cl 2 compound revealed that the dpa ligand most likely undergoes a longitudinal shuffling, shifting form coordination mode III to mode IV, where the central N a bridges the quadruply bonded metal atoms, to mode III which allows for metalation to occur, scheme 3 [79]. For Cr 2 (dpa)4 , refluxing THF provides enough heat to accomplish this rearrangement.…”
mentioning
confidence: 99%